Persaksian Talak: Perspektif Ulama Sunni dan Syi'ah Imamiyah - Trigiyatno, Ali (Al-Manahij: Jurnal Kajian Hukum Islam, 2020)
In general, Islamic scholars have the same spirit in addressing the occurrence of divorce, namely the desire to make divorce difficult. However, on the other hand, there appears to be an inconsistency in this matter, where when reading fiqh books in a Sunni environment it seems that they facilitate divorce. As in the case of divorce testimony, Sunni ulama legalize the fall of divorce without witnesses, while among Shia clerics, they make divorce more difficult by requiring two fair witnesses to the legality of a divorce. This article aims to compare the two different views of Sunni and Shia scholars regarding divorce testimony in order to determine a stronger and more beneficial opinion. The result of the research proves that the arguments of the Shia ulama which oblige two witnesses to validate divorce are stronger and more beneficial. This opinion also makes it more difficult for the possibility of divorce to fall, and in its development, it is used in the legislation of Muslim countries by requiring divorce in front of a court session where at least two witnesses are certain to witness.